Preparation and characterization of superior hydrophilic PVDF/DA membranes by the self-polymerization approach of dopamine - Li, Shaofeng; Zhang, Meilin; Sun, Jian; Sun, Jianping; Wang, Ying (Frontiers in Chemistry, 2023)
The objective of this study was to improve the performance of polyvinylidene fluoride (PVDF) membranes using the self-polymerization, strong adhesion properties, and biocompatible effects of dopamine (DA), and to optimize the conditions of PVDF/DA membrane modification by using response surface methodology (RSM). The PVDF/DA membrane modification conditions were simulated and optimized using RSM, and the experimental design was used to investigate three main parameters. The results showed that the DA solution concentration of 1.65 g/L, the coating time of 4.5 h, the post-treatment temperature of 25 ℃, the contact angle decreased from 69° to 33.9°, and the pure water flux on the PVDF/DA membrane was higher than that on the original membrane. The absolute value of the relative error between the actual and predicted values is only 3.36%. In the MBR parallel comparison test, compared with the PVDF/DA membrane, the total amount of extracellular polymers (EPS) of the PVDF membrane increased by1.46 times and the polysaccharide increased by 1.56 times, which further showed that the PVDF/DA modified membrane had the excellent anti-pollution ability. Through Alpha diversity analysis, the biodiversity detected on PVDF/DA membranes was higher than that of PVDF membranes, which further proved its good bio-adhesion ability.